Stock Assessment of Long Whisker Catfish (Mystus gulio): Ensuring the Fisheries’ Sustainability in the Sundarbans Mangrove, Bangladesh - Md. Tanvir Rahman Ovi; Tanni Sarkar; Dwipika Gope; Rayhan Ahmod; Sanzib Kumar Barman; Md. Mostafa Shamsuzzaman; Mohammad Mojibul Hoque Mozumder; Petra Schneider; Partho Protim Barman (Fishes, 2025)
The world’s largest mangrove, Sundarbans, Bangladesh, is the habitat of the euryhaline catfish Nona Tengra (Mystus gulio). This study aimed to assess the stock status of M. gulio and provide reference points for sustainable fisheries’ management. One-year length–frequency (LF) data were collected from the Sundarbans region of Bangladesh and analyzed using the Length-Based Bayesian Biomass (LBB) method and the Length-Based Spawning Potential Ratio (LBSPR) model. The findings showed healthy biomass (B/BMSY = 1.2), with 57% of the wild stock of this species being harvested (B/B0 = 0.43). The calculated fishing mortality ratio indicated the underfishing conditions (F/M = 0.9). Safe exploitation (E = 0.46) was depicted, as E was smaller than the permitted level of 0.5. The value of capture length (Lc = 12.8 cm) was larger than the optimum capture length (Lc_opt = 10.0 cm) and the optimum length for maximum yield per recruit (Lopt = 12.0 cm) and larger than the maturity length (Lm = 9.16 cm), indicating the capture of mature individuals. The calculated Spawning Potential Ratio (SPR = 48%) was higher than the target reference points (SPR = 40%). This research evaluated the sustainable stock status. Although the margin between Lc_opt and Lm is very narrow, setting the minimum capture size at Lopt would be a conservative buffer to ensure long-term sustainability. The recommended minimum harvest size is 12 cm for M. gulio. Current fishing gear selectivity can ensure the sustainability of M. gulio in Sundarbans, Bangladesh; however, maintaining current fishing practice through careful management is suggested. Further assessments with length-based and other low-data methods should be conducted to refine exploitation estimates and trends.